The metabolic clinical risk score as a new prognostic model for surgical decision‐making in patients with colorectal liver metastases. Issue 2 (12th November 2019) - Duran Derijckere, Ivan; Levillain, Hugo; Bohlok, Ali; Mathey, Celine; Nezri, Jonathan; Muteganya, Raoul; Trotta, Nicola; Lucidi, Valerio; Bouazza, Fikri; Germanova, Desislava; Van Simaeys, Gaetan; Goldman, Serge; et al.
Abstract: Background and Objectives: Selection for surgery in patients with colorectal liver metastases (CRLM) remains inaccurate. We evaluated if CRLM baseline metabolic characteristics, assessed by [18]F‐fluorodeoxyglucose‐positron emission tomography/computed tomography ( 18 FDG‐PET/CT), could predict postoperative outcomes. Methods: In a retrospective series of patients undergoing surgery for CRLM, we defined two groups: the long‐term survival (LTS) and early relapse (ER) groups, where the postoperative recurrence‐free survivals were ≥5 years or <1 year, respectively. We analyzed the patients in whom baseline 18 FDG‐PET/CT was available. Clinicopathologic parameters, clinical risk score (CRS), and baseline 18 FDG‐PET/CT characteristics were compared between LTS and ER groups. A metabolic CRS (mCRS) was implemented, adding one point to the standard five‐point CRS when the highest tumor standardized uptake values (SUVmax )/normal liver mean SUV (SUVmean(liver) ) ratios were >4.3, defining low‐ and high‐risk mCRS by scores of 0 to 2 and 3 to 6, respectively. Results: From a series of 450 patients operated for CRLM (mean follow‐up of 58 months), we included for analysis 23 and 30 patients in the LTS and ER groups, respectively. Clinicopathologic parameters and CRS were similar in the LTS and ER groups. Median SUVmax /SUVmean(liver) ratios were higher in ER vs LTS patients (4.2 and 2.8, P = .008, respectively). mCRS was increased in ER patients ( P = .024); 61% of LTS patients had low‐risk mCRS and 73% of the ER patients had high‐risk mCRS ( P = .023). Conclusions: 18 FDG‐PET/CT characteristics combined with traditional CRS may represent a new tool to improve selection for surgery in patients with CRLM.